2009
DOI: 10.1080/15374410802575354
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Parental Psychological Control and Childhood Relational Aggression: Reciprocal in Nature?

Abstract: Using a cross-lagged panel design, this study examined the directionality of relations between parental psychological control and child relational aggression. Data were collected from a proportionally stratified sample of 600 Flemish 8- to 10-year-old children at 3 measurement points with 1-year intervals. Reciprocal effects were evident in mother-child dyads. Maternal psychological control was positively related to child relational aggression 1 year later, and child relational aggression was positively relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 44 publications
3
37
1
3
Order By: Relevance
“…In contrast, high levels of psychological control are related to emerging adults' low self-esteem and social competence as well as high levels of depression, anxiety, and externalizing problems. Research also examines the relationship between parental psychological control and children's use of relational aggression (i.e., behaviors that harm others by damaging or threatening to damage relationships, feelings of acceptance, friendships, or group inclusion [15]), and it was found that maternal psychological control is related positively to children's relational aggression at home 1 year later.…”
Section: Disciplinementioning
confidence: 98%
“…In contrast, high levels of psychological control are related to emerging adults' low self-esteem and social competence as well as high levels of depression, anxiety, and externalizing problems. Research also examines the relationship between parental psychological control and children's use of relational aggression (i.e., behaviors that harm others by damaging or threatening to damage relationships, feelings of acceptance, friendships, or group inclusion [15]), and it was found that maternal psychological control is related positively to children's relational aggression at home 1 year later.…”
Section: Disciplinementioning
confidence: 98%
“…Penelitian-penelitian yang sudah ada sebelumnya mengenai altruisme dan bullying pada remaja, mengkaitkannya dengan pengaruh pengasuhan yang diterima dari orangtuanya Kuppens, Laurent, Heyvaert, & Oghena, 2013;Mount, 2002;Rahmawati, 2016). Berdasarkan paparan tersebut, dapat ditengarai bila kajian-kajian mengenai parenting dalam kaitannya dengan altruisme maupun bullying sudah cukup banyak dilakukan.…”
Section: Pendahuluanunclassified
“…Pengasuhan yang diterima anak sejak dini hingga masa remaja akan mengembangkan nilai-nilai tertentu dalam keluarga. Keluarga yang hangat dan menyontohkan kepedulian kepada orang lain akan mendorong anak untuk memiliki rasa empati, tanggung jawab serta kesediaan untuk berbagi Kuppens, Laurent, Heyvaert, & Oghena, 2013;Muth, 2012). Hal ini dikarenakan lingkungan keluarga akan memengaruhi tercapainya perkembangan optimal pada penanaman nilai yang dimiliki oleh anak (Hoghughi, 2004), termasuk di dalamnya tingkah laku altruisme dan bullying (Beecler, 2011;Crapanzano, 2010).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…However, when understanding the association between the reaction of parents and children to traumatic events, one should consider two important issues: first, that the influence in the parent-child dyad could be bidirectional, that is the reaction of the child may also influence that of the parents, and second, that a genetic susceptibility for developing posttraumatic stress may be transmitted to the children by the parents 14 . To support the importance of genetic contributions to the child's reactions to trauma, research has found that PTSD risk is associated with an interaction between genetic dispositions and early experiences 15 and with a combination of a biological, oxytocin-vasopressin genotype and sensitive caregiving by mothers during evocation of a traumatic event 16 .…”
Section: Outcome and Moderating Factorsmentioning
confidence: 99%